Effectiveness and Safety of Therapeutic Vaccines for Precancerous Cervical Lesions: A Systematic Review and Meta-Analysis - Cai, Shan; Tan, Xiaoyu; Miao, Ke; Li, Dantong; Cheng, Si; Li, Pei; Zeng, Xueyang; Sun, Feng (Frontiers in Oncology, 2022)
Objective This study systematically evaluated the effectiveness and safety of therapeutic vaccines for precancerous cervical lesions, providing evidence for future research. Methods We systematically searched the literature in 10 databases from inception to February 18, 2021. Studies on the effectiveness and safety of therapeutic vaccines for precancerous cervical lesions were included. Then, we calculated the overall incidence rates of four outcomes, for which we used the risk ratio (RR) and 95% confidence interval (95% CI) to describe the effects of high-grade squamous intraepithelial lesions (HSILs) on recurrence. Results A total of 39 studies were included, all reported in English, published from 1989 to 2021 in 16 countries. The studies covered 22,865 women aged 15–65 years, with a total of 5,794 vaccinated, and 21 vaccines were divided into six types. Meta-analysis showed that the overall incidence rate of HSIL regression in vaccine therapies was 62.48% [95% CI (42.80, 80.41)], with the highest rate being 72.32% for viral vector vaccines [95% CI (29.33, 99.51)]. Similarly, the overall incidence rates of HPV and HPV16/18 clearance by vaccines were 48.59% [95% CI (32.68, 64.64)] and 47.37% [95% CI (38.00, 56.81)], respectively, with the highest rates being 68.18% [95% CI (45.13, 86.14)] for bacterial vector vaccines and 55.14% [95% CI (42.31, 67.66)] for DNA-based vaccines. In addition, a comprehensive analysis indicated that virus-like particle vaccines after conization reduced the risk of HSIL recurrence with statistical significance compared to conization alone [RR = 0.46; 95% CI (0.29, 0.74)]. Regarding safety, only four studies reported a few severe adverse events, indicating that vaccines for precancerous cervical lesions are generally safe. Conclusion Virus-like particle vaccines as an adjuvant immunotherapy for conization can significantly reduce the risk of HSIL recurrence. Most therapeutic vaccines have direct therapeutic effects on precancerous lesions, and the effectiveness in HSIL regression, clearance of HPV, and clearance of HPV16/18 is great with good safety. That is, therapeutic vaccines have good development potential and are worthy of further research. Systematic Review Registration PROSPERO https://www.crd.york.ac.uk/PROSPERO/, CRD42021275452.